2008
DOI: 10.1007/s11414-007-9093-z
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Program Predictors of Attrition from VA Substance Use Treatment

Abstract: The study investigated patient- and program-level variables associated with attrition from intensive outpatient (IOP) substance use treatment in a national VA sample. National databases were used to identify a recent cohort of veterans receiving intensive IOP substance use treatment. Attrition was defined as receiving less than five visits of IOP treatment. Patient-level variables examined included age, gender, race, and psychiatric and medical comorbidities. Program-level variables examined included the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 27 publications
2
14
2
1
Order By: Relevance
“…However, other studies found no significant differences in retention rates based on race, particularly after controlling for psychosocial factors (Booth, Corsi, & Mikulich-Gilbertson, 2004;Brewer, Catalano, Haggerty, Gainey, & Fleming, 1998;Curran, Stecker, Xiaotong, & Booth, 2009;Howard, LaVeist, & McCaughrin, 1996;Justus, Burling, & Weingardt, 2006;Knight, Logan, & Simpson, 2001;Magura, Nwakeze, & Demsky, 1998;Sayre et al, 2002). In this current study of the LGBT population, there were no differences in program completion rates based on race.…”
Section: Discussioncontrasting
confidence: 80%
“…However, other studies found no significant differences in retention rates based on race, particularly after controlling for psychosocial factors (Booth, Corsi, & Mikulich-Gilbertson, 2004;Brewer, Catalano, Haggerty, Gainey, & Fleming, 1998;Curran, Stecker, Xiaotong, & Booth, 2009;Howard, LaVeist, & McCaughrin, 1996;Justus, Burling, & Weingardt, 2006;Knight, Logan, & Simpson, 2001;Magura, Nwakeze, & Demsky, 1998;Sayre et al, 2002). In this current study of the LGBT population, there were no differences in program completion rates based on race.…”
Section: Discussioncontrasting
confidence: 80%
“…Two papers in this special issue study utilization of services in vastly differing populations: veterans in VA intensive outpatient treatment 6 and adolescents in community-based substance abuse outpatient clinics. 5 Both papers address significant clinical issues for their respective populations that may have adverse effects upon treatment outcomes: early attrition from VA services and co-occurring mental health problems in adolescents.…”
Section: Utilizationmentioning
confidence: 99%
“…If programs are to enhance their quality of care, they must organize their service delivery systems appropriately. The paper of Curran et al 6 examines both program-level and individual factors associated with early attrition, thus providing insight into organizational factors that may affect patient behavior.…”
Section: Utilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Those who remained in the treatment net, significant proportion (45.7%) of patients were improved. High dropout rate has also been observed in the studies from the US and the rate of dropout after first contact is as high as 42% [13]. Half of the subjects were failed to be engaged in the treatment because of their short follow up duration [13].…”
mentioning
confidence: 95%